The Relationship Between Anxiety Levels And Student Academic Achievement At SMK X Jakarta - Apita Nur Rahma; Rima Berlian Putri; Maria Susila Sumartiningsih; Roza Indra Yeni (Jurnal Life Birth, 2025)
Background: Anxiety is a psychological factor that can affect students' learning ability and academic achievement. Vocational High School (SMK) students generally face high academic pressure and demands for practical skills, which have the potential to cause anxiety. The purpose of this study is to determine the relationship between anxiety levels and students' academic achievement at SMK X Jakarta. This study uses a quantitative approach with an observational analytical design and a cross-sectional approach method. The population in the study amounted to 65 students, all of whom were sampled using a total sampling technique. Data collection was carried out using validated instruments, then analyzed using the Spearman Rho correlation test. Results: The analysis showed a very weak positive relationship between anxiety levels and academic achievement, with a correlation coefficient (r) of 0.006 and a significance value of 0.965 (p > 0.05). This value indicates that statistically there is no significant relationship between anxiety levels and students' academic achievement at SMK X Jakarta. The conclusion is that anxiety does not have a significant effect on academic achievement in the context of this study. These results can be a consideration for schools in developing learning strategies and psychological support for students, although other factors beyond anxiety still need to be considered as determinants of academic success